Phase 2 study of NAB-paclitaxel in SensiTivE and refractory relapsed small cell lung cancer (SCLC) (NABSTER TRIAL) - Gelsomino, Francesco (Br J Cancer, 2020)
BACKGROUND: Despite sensitivity to first-line chemotherapy, most small-cell lung cancer (SCLC) patients relapse. In this setting, topotecan demonstrated modest activity with significant toxicity. Paclitaxel was also active. This study was designed to evaluate activity and safety of nab-paclitaxel in relapsed SCLC. METHODS: In this multicentre prospective Phase 2 trial, patients with refractory or sensitive SCLC progressed to first-line platinum-based chemotherapy received nab-paclitaxel 100 mg/smq on days 1, 8, 15 every 4 weeks up to six cycles, progressive disease or intolerable toxicity. Primary endpoint was investigator-assessed objective tumour response. Secondary endpoints were toxicity, progression-free survival (PFS) and overall survival (OS). RESULTS: Of the 68 patients treated, partial response was 8% in the refractory cohort and 14% in the sensitive cohort. Most common toxicities of any grade were fatigue (54%), anaemia (38%), neutropenia (29%), leukopenia (26%) and diarrhoea (21%). Median PFS was similar in both refractory (1.8 months) and sensitive cohorts (1.9 months), while median OS was longer in sensitive one (6.6 versus 3.6 months). CONCLUSIONS: Although nab-paclitaxel has shown some modest anti-tumour activity in relapsed SCLC, associated with a favourable toxicity profile, the primary end-point of the study was not met. CLINICAL TRIAL REGISTRATION: Clinical Trial registration number is ClinicalTrials.gov Identifier: NCT03219762.